Sensitivitas, spesifisitas, nilai prediksi positif, nilai prediksi negatif dan akurasi metode Lateral Flow Immuno Assay (LFIA) dengan mikroskopis untuk diagnosis gonore - Bambang Supriyanta; Budi Setiawan (Pusat Unggulan Iptek (PUI) Poltekkes Kemenkes Yogyakarta, 2021)
Gonorrhea is a significant health problem, especially in men with high-risk sexual behavior. The gold standard examination for the diagnosis of gonorrhea is a microscopic examination, culture, and nucleic acid amplification test. However, nucleic acid amplification and culture tests are difficult to carry out in the Public Health Center laboratory, due to limited facilities and human resources. JusChek Gonorrhea Rapid Test (JCGRT) is an examination using the Lateral Flow Immuno Assay (LFIA) method which is relatively easy, more practical, does not require sophisticated equipment, is fast in processing, and can provide results in a short time. This study was to determine the sensitivity, specificity, Positive Predictive Value, Negative Predictive Value, and accuracy of JCGRT using the LFIA method compared to microscopic examination for the diagnosis of gonorrhea. This research is a descriptive-analytic study with a diagnostic test design located in a public health center in Yogyakarta, Indonesia. Based on the results of the study, the sensitivity value was 92%, specificity 96%, Positive Predictive Value 95.83%, Negative Predictive Value 92.31%, and Accuracy of 94% JCGRT LFIA method compared with microscopic examination. JCGRT shows good sensitivity and specificity for the diagnosis of gonorrhea. Its use is quite practical, it is recommended that health care facilities with limited facilities can use this method.